(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the ideologemes of Islam in modern Kyrgyzstan. The author analyzes the historical roots of Islam in the region, starting with its emergence in the 8th century, the influence of the Soviet period, and the revival of Islam after independence in 1991. Issues such as radicalization and extremism, the role of the state in regulating religious life, the development of state policy on religious education, and the influence of international Islamic organizations are explored. The article emphasizes the need to maintain a balance between traditional religious values and modern democratic principles. This work provides a current perspective on the complex interaction of religion, society, and the state in Kyrgyzstan.